2023
DOI: 10.3390/app13095591
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Remodelling the As-Built Documentation of a Railway Construction into the BIM and GIS Environment

Abstract: Building Information Modelling (BIM) is a modern approach to managing the process of preparation, realization and operation of building objects including their documentation throughout their life cycle, based on database agenda platform. The aim of our research is to analyze and innovate existing engineering procedures with the aim: 1. to remodel the existing CAD documentation into BIM for the purpose of public procurement, 2. to provide guaranteed data to the IS of the Digital Map of Public Administration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…The proposed method solves a problem in the field of reverse engineering, where the actual documentation of buildings is mainly obtained manually with minimal automated support (libraries of elements). Although laser scanning and satellite measurement methods have recently been preferred- [62,63]-practice has confirmed that these methods cannot do without the classic measuring by total stations.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method solves a problem in the field of reverse engineering, where the actual documentation of buildings is mainly obtained manually with minimal automated support (libraries of elements). Although laser scanning and satellite measurement methods have recently been preferred- [62,63]-practice has confirmed that these methods cannot do without the classic measuring by total stations.…”
Section: Discussionmentioning
confidence: 99%